The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1074/jbc.m700501200
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA (miRNA) Transcriptome of Mouse Retina and Identification of a Sensory Organ-specific miRNA Cluster

Abstract: Although microRNAs (miRNAs) provide a newly recognized level of regulation of gene expression, the miRNA transcriptome of the retina and the contributions of miRNAs to retinal development and function are largely unknown. To begin to understand the functions of miRNAs in retina, we compared miRNA expression profiles in adult mouse retina, brain, and heart by microarray analysis. Our results show that at least 78 miRNAs are expressed in adult mouse retina, 21 of which are potentially retina-specific. Among thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
513
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(552 citation statements)
references
References 117 publications
32
513
0
1
Order By: Relevance
“…In accordance with the effectiveness of miR-182 suppression, mRNA levels of its direct targets ADCY6 (Xu et al, 2007) and FOXO3 (Segura et al, 2009) were found to be upregulated in the tumors of anti-miR-182-treated mice in both experimental settings ( Figure 2b). Moreover, we also observed an increase in FOXO3 protein expression in the tumors of anti-miR-182-treated mice by immunohistochemistry ( Figure 2c).…”
Section: Suppression Of Mir-182 and Concomitant Upregulation Of Mir-1supporting
confidence: 63%
“…In accordance with the effectiveness of miR-182 suppression, mRNA levels of its direct targets ADCY6 (Xu et al, 2007) and FOXO3 (Segura et al, 2009) were found to be upregulated in the tumors of anti-miR-182-treated mice in both experimental settings ( Figure 2b). Moreover, we also observed an increase in FOXO3 protein expression in the tumors of anti-miR-182-treated mice by immunohistochemistry ( Figure 2c).…”
Section: Suppression Of Mir-182 and Concomitant Upregulation Of Mir-1supporting
confidence: 63%
“…These miRNAs also highly correlated with hsa-miR-182 by being transcribed as a single polycistronic primarymiRNA. 37 Hsa-miR-96 was also found upregulated in primary cells from chronic myeloid leukemia 38 and in hepatocellular tumors. 39 Moreover, we found hsa-miR-96 to be associated with Gleason score and biochemical relapse.…”
Section: Discussionmentioning
confidence: 98%
“…Several recent studies have characterized miRNAs expressed in the mammalian retina using microarray-based expression profiling and/or in situ hybridization (Deo et al, 2006;Ryan et al, 2006;Arora et al, 2007;Karali et al, 2007;Loscher et al, 2007;Xu et al, 2007). Studies in zebrafish have also identified several miRNAs with cellspecific expression in retina (Kapsimali et al, 2007).…”
Section: Mirnas Retinal Cell-specific Mirnasmentioning
confidence: 99%
“…In zebrafish, miR-9 and miR-92 are highly expressed in the mitotically active ciliary marginal zone (CMZ), and are likely to be progenitor-enriched in mouse (Kapsimali et al, 2007). The targets of these embryonic and early postnatally-enriched mouse miRNAs have yet to be investigated, and no key developmental regulatory genes have yet (Loscher et al, 2007;Xu et al, 2007), species in which retinal expression is observed (Arora et al, 2007;Kapsimali et al, 2007;Karali et al, 2007;Loscher et al, 2007;Xu et al, 2007), developmental expression pattern , mouse cellular expression pattern (Karali et al, 2007;Loscher et al, 2007;Xu et al, 2007), zebrafish cellular expression pattern (Kapsimali et al, 2007), cellular targets (Arora et al, 2007;Xu et al, 2007), expression change in rd animals (Loscher et al, 2007). AC, amacrine cells; CMZ, ciliary marginal zone; GC, ganglion cells; GCL, ganglion cell layer; HC, horizontal cells; HD, homeodomain; INL, inner nuclear layer; MG, Muller glia; NA, not applicable; ND, not determined; NHR, nuclear hormone receptor; ONL, outer nuclear layer; Prog, retinal progenitors; s(prefix) Ď­ subset (cell type).…”
Section: Retinal Mirnas In Cell Fate Determinationmentioning
confidence: 99%